Food insecurity in relation to governance in Uganda - KATONGOLE TAUFIQ, SSALI ISMAIL (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The study’s overarching objective was to examine the causes of food insecurity in relation to governance and suggest ways to combat the problem and better the population’s lives.Method: Documentary review is used as a qualitative research method in this exploratory study to glean information about food insecurity and governance laws already on the books in Uganda. Data is analyzed using both descriptive and interpretive approaches.Findings: Deforestation and land disputes are two examples of government failures contributing to food insecurity. Increased refugee movement is a costly problem for the country, but it benefits a select few within the relevant institutions. Financing alternatives that generate new jobs for people and boost the availability of healthy, nutritious food are the key to solving all of these problems. There have been several studies done on how to best improve food insecurity and governance ethics in Uganda, and this is one of them.Implications/Novel Contribution: This research adds to the body of knowledge on partnering to increase government revenue, enhance governance, combat food insecurity, and decrease unemployment.